Upaya Meningkatkan Aktivitas dan Hasil Belajar Ekonomi Pokok Bahasan Kerjasama Ekonomi Internasional Menggunakan Model Pembelajaran Jigsaw Siswa Kelas XII IPS 3 SMAN 3 Kotabumi Tahun Pelajaran 2018—2019 - Yenniati Yenniati (Universitas Muhammadiyah Kotabumi, 2019)
This study aims to improve economic learning activities and outcomes using the Jigsaw learning model on international economic cooperation material for class XII IPS 3 students of SMA Negeri 3 Kotabumi in the 2018-2019 academic year. This research is a classroom action research, which was conducted to students of class XII IPS 3 of SMAN 3 kotabumi in the 2018-2019 academic year. In this study tested the use of Jigsaw learning models on international economic cooperation material to determine its effect on student learning outcomes. The study was divided into 2 cycles, namely for the material of cooperation between countries in the economic field and the multilateral economic cooperation body. Data collection techniques with cognitive tests and student attitude questionnaires obtained from each cycle, the results were analyzed whether there was an increase in each cycle. The results of this study indicate that, the use of Jigsaw learning models on international economic cooperation material can improve student learning outcomes in class XII IPS 3. Student learning outcomes have increased by 58% from cycle I to cycle II, while student activity based on questionnaires has increased in cycle II where students, more disciplined, cooperative, polite and tolerant in learning. Thus the use of Jigsaw learning models in the material of international economic cooperation can improve the economic learning outcomes of students of class XII IPS 3 at SMAN 3 Kotabumi in the academic year 2018-2019.